2018
DOI: 10.3390/su10124597
|View full text |Cite
|
Sign up to set email alerts
|

CSR and Firm Value: Evidence from China

Abstract: This study attempts to investigate the influence of corporate social responsibility (CSR) on firm value. Drawing upon stakeholder theory and a resource-based view, we argue that corporate social responsibility is expected to positively affect firm value because it helps firms gain positive stakeholder responses. Based on longitudinal data of Chinese manufacturing firms listed at Shanghai and Shenzhen Stock Exchange between 2010 and 2015, we use multiple linear regression to find that corporate social responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 92 publications
(133 reference statements)
8
56
0
10
Order By: Relevance
“…The measurements of these six variables were directly obtained from Hexun CSR dataset, which provides the annual CSR rating scores of all Chinese listed companies since 2010, the year after Chinese listed companies were officially required to issue their CSR reports. Hexun CSR dataset is regarded as the most comprehensive, latest, authoritative CSR database in China, and thus has been widely applied in relevant empirical studies [101,102].…”
Section: Dependent Variablesmentioning
confidence: 99%
“…The measurements of these six variables were directly obtained from Hexun CSR dataset, which provides the annual CSR rating scores of all Chinese listed companies since 2010, the year after Chinese listed companies were officially required to issue their CSR reports. Hexun CSR dataset is regarded as the most comprehensive, latest, authoritative CSR database in China, and thus has been widely applied in relevant empirical studies [101,102].…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Carroll (2015) indicated that CSR is growing in relevance in modern business practice. Integrating CSR into business practices can contribute to an increase in company value (Hu et al, 2018). Therefore, companies that engage in CSR practices are more profitable (Hategan et al, 2018).…”
Section: Corporate Social Responsibility Practicesmentioning
confidence: 99%
“…Oh, Hong, and Hwang (2017) indicated that engaging in CSR behaviors can be a primary tool in attaining sustainable growth. However, the value of CSR can be affected through stakeholder perceptions (Hu, Chen, Shao, & Gao, 2018). To increase consumer value, businesses must understand which dimensions of CSR (economic, legal, ethical, or philanthropic) that various generations perceive to be most significant.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some scholars agree with the reputation effect of CEP, but firms have difficulty internalizing the effects to complement the costs [37]. The alternative view argues that firms can cultivate rare, unduplicated, and irreplaceable resources in the process of increasing CEP based on instrument stakeholder theory and resource-based views [38], thus positively affecting firm value [8]. Meanwhile, Singh et al [39] thought that getting accreditation in environmental programs such as ISO 14000 standards enables firms to achieve legitimacy by signaling to stakeholders their internal emphasis on environmental performance and pressing their supply chain partners to obtain similar accreditation.…”
Section: Consequences Of Cepmentioning
confidence: 99%
“…When we focus on corporate environment practices, only 33% of listed firms in China choose to publish social and environmental reports [6]; most firms doubt that this action will detract from firm value [7]. Herein, the corporate value mainly refers to the corporate market value [8], since it has less discretionary space, compared to the accounting-based variable [9]. Meanwhile, it can better predict firm performance in the long run, therefore testing whether a certain corporate environmental strategy is sustainable [10].…”
Section: Introductionmentioning
confidence: 99%